Implementasi Kebijakan Kepala Desa dalam Penanganan Masalah Sosial Kemasyarakatan di Desa Toyado Kecamatan Lage Kabupaten Poso - Syuaib, Mohammad Rusli (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study aims to determine the implementation of village head policies in handling social and community problems in Toyado Village, Lage District, Poso Regency and. In this study, a descriptive type of research is used that provides a detailed and clear description of the problem being studied. To find out the value of an independent variable, either one or more variables without making a comparison or connecting one variable with another. The results of the study show that public order is not completely good where theft cases still occur, especially against community livestock in Toyado Village. So that efforts to maintain public order by coordinating with the police and the TNI in anticipating opportunities or potentials that will cause problems with quick handling. Social order in Toyado Village is generally good, but there are still teenagers who deviate from their associations such as juvenile delinquency as a result of the influence of inappropriate use of cell phones. The Head of Toyado Village has carried out preventive measures that are carried out by involving community leaders in overcoming violations that occur. The Head of Toyado Village has implemented sanctions but needs to implement stricter rules which of course involve religious leaders, community leaders, traditional leaders and youth leaders. Factors that affect the implementation of village head policies in handling social and community problems in Toyado Village, Lage District, Poso Regency are the limitations of the ability and skills of village officials and lack of community participation.